838 Gamma Knife Stereotactic Radiosurgery Retreatment of Trigeminal Neuralgia: Prognostic Factors and Clinical Outcomes. (April 2023) - Ramanathan, Siddharth; Loving, Bailey; Fontanesi, James; Grills, Inga S.; Michael, Daniel B.; Chen, Peter; Fahim, Daniel K.
Abstract : INTRODUCTION: Trigeminal neuralgia(TN) is a debilitating nerve disorder affecting approximately 4.5 per 100, 000 people annually. While medical management is the first line of treatment, Gamma Knife Stereotactic Radiosurgery(GKSRS) may be used. Long-term outcomes after GKSRS retreatment are not well elucidated. METHODS: Of the 168 patients treated since 2012 at our institution, 149 had adequate follow-up data, and 53(40.4%) received 2 treatments. The Barrow Neurological Institute (BNI) pain intensity score was used to grade pain. Pain relief was defined as post-GKSRS BNI score of I-III. Treatment failure was defined as post-GKSRS score of IV-V without pain-relief. Pain-recurrence was defined as a post-GKSRS score of IV-V after achieving pain-relief. Univariable analyses were performed to examine the effects of multiple factors on outcomes. RESULTS: Median follow-up was 15(1-63) months; 136(90%) and 49(83.0%) patients achieved pain-relief after T1 and T2 respectively. Median time to pain-relief was 3 months and 1 month after T1 and T2 respectively. Median freedom from pain-recurrence was 24.0 months and 13.7 months following T1 and T2 respectively; 44 (30.0%) and 6 (12.2%) patients developed pain-recurrence following T1 and T2 respectively. High KPS score, V1+V2 pain distribution, and absence of mastication deficits reduced the risk of T1 treatment failure by 21%, 58%, and 54% respectively(p<0.05). Patients with lower BNI scores after T1 had a 39% reduced risk of T2 failure(p<0.001); 2(1.3%) and 4(6.8%) patients developed facial and/or mastication deficits following T1 and T2 respectively. Neither isocenter location nor dose affected outcomes. CONCLUSIONS: GKSRS remains an effective treatment for patients with refractory TN. Our data show that patients who fail or recur after T1 may still receive symptomatic relief following T2 with minimal toxicity. Abstract not yet presented, but accepted for presentation at ASTRO 2022